Role of Magnetic Resonance Spectroscopy and Diffusion-weighted Imaging in the Evaluation of Supratentorial Brain Tumours with Histopathology Correlation at a Tertiary Care Hospital: An Observational Study - Kotireddy Pavan Kumar Reddy; Rajalingam Venkat Sai; R. Archana; Sarala Devi; Sunitha Bajaj; Valluru Naga Lakshmi Vaishali (Journal of Medical Evidence)
Background: Traditional magnetic resonance imaging (MRI) may face challenges in accurately discerning supratentorial malignancies. However, advanced techniques such as diffusion-weighted imaging (DWI) and magnetic resonance spectroscopy (MRS) have significantly enhanced diagnostic accuracy. Thus, the study aimed to evaluate the effectiveness of these non-invasive diagnostic methods in patients with suspected intracranial lesions. Materials and Methods: In this prospective observational study at Osmania General and Allied Hospitals, 40 eligible patients were enrolled. After applying the inclusion and exclusion criteria, MRI examinations were conducted at two hospitals utilising GE 1.5T and PHILIPS 1.5T 32-channel machines. Standardised brain sequences, encompassing T1- and T2-weighted scans, DWI, gradient-recalled echo and fluid-attenuated inversion recovery imaging, were systematically performed. In addition, post-contrast administration and contrast-enhanced MRS were employed. Results: In this study, a higher tumour incidence was observed in males (52%) compared to females (48%). The choline/creatine (CHO/Cr) ratio revealed more cases below 1.5 and fewer at the 3.1–3.5 level. Perilesional CHO/Cr ratio had the highest cases (21) at 1.1–2.0 and the lowest (2) at 3.1–4.0. Further analysis revealed significant differences in the mean CHO/Cr ratio amongst primary low-grade (1.8), primary high-grade (3.91) and metastatic tumours (7.23). The mean choline/N-acetyl aspartate (NAA) ratio also differed significantly amongst these tumour types, with choline/NAA and CHO/Cr ratios indicating statistical significance in distinguishing primary low-grade tumours. In addition, mean apparent diffusion coefficient values showed significant differences between primary low-grade tumours (1.1), primary high-grade tumours (0.87) and metastasis (0.855). Conclusion: This study underscores gender-related differences in supratentorial tumour susceptibility and highlights distinct tumour distributions based on grades. These findings emphasise the significance of considering gender, age and histopathological attributes when evaluating supratentorial tumours.